INFLUENCE OF CHROMIUM SULPHATE AND MIMOSA (ACACIA DEALBATA) POWDER ON THE QUALITY ATTRIBUTES OF LEATHER PRODUCED FROM THE RUMEN OF CATTLE, SHEEP AND GOAT - Jantiku, Hamman J.; Ekpa, E.; Bata, I.; Ijasini, J. A.; Kperun, T. N. (FUDMA JOURNAL OF SCIENCES, 2024)
The study was carried out to investigate the feasibility of converting the rumen of ruminant animals into leather. Rumen samples from cattle, sheep and goats where subjected to two tanning methods: chromium sulphate and mimosa powder, with five (5) replicates under controlled conditions. Chromium sulphate tanning procedures involved cleaning, liming, de-liming, degreasing, fleshing, drenching, pickling, tanning, basification, aging, re-tanning, neutralization and fat liquoring while the mimosa powder tanning procedures included: cleaning, liming, de-liming, degreasing, fleshing, drenching, tanning and fat liquoring. The mechanical operation like fixing, staking and toggling were also carried out for both tanning procedures. The resulting leathers underwent a series of tests which included: thickness, tensile strength, percentage elongation, ball burst test, water absorption, shrinkage temperature, stitch and tear, permeability to water vapour and apparent density. The results obtained showed that thickness, tensile strength, percentage elongation, shrinkage temperature and water absorption differed significant (P0.05) affected. The outcome of this study establish that rumen from cattle, sheep and goat can be processed into leather for many end uses. Leather quality is affected by rumen type and tanning agent. Cattle rumen tanned with chromium sulphate exhibited the best performance while mimosa powder tanned rumen leathers offers a sustainable and natural alternative. Due to its unique texture, rumen leather can be crafted into various items including key cases, purses, bracelets and...
Keywords: Rumen; Tanning; Chromium Sulphate; Mimosa Powder; Leather